Pengaruh Kebijakan Efisiensi Anggaran Terhadap Peningkatan Kinerja Keuangan Di BKPSDM Kabupaten Bantul - Riswanto, Riswanto; Firdarini, Khoirunnisa Cahya (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Public financial management requires regional organizations to use budgets efficiently to support organizational goals and public services. In practice, local governments need to implement budget efficiency policies to improve the quality of spending while maintaining the financial performance of the organization. This study aims to analyze the implementation of budget efficiency policies and their implications for financial performance at the Bantul Regency Civil Service and Human Resource Development Agency. The study uses a qualitative descriptive approach to examine the implementation of budget efficiency policies and their impact on organizational financial management. Data were collected through interviews, observations, and documentation of twelve informants involved in budget management at the agency. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing with validity testing using source and technique triangulation. The results of the study indicate that the implementation of budget efficiency policies encourages more selective spending, strengthens expenditure control, and improves alignment between budget planning and realization. These conditions contribute to improved organizational financial performance and strengthen the accountability of regional financial management. These findings indicate that the implementation of appropriate budget efficiency policies can improve the effectiveness of financial management and support the implementation of performance-based budgeting in local government agencies.